2011
DOI: 10.1098/rsta.2011.0271
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Cerenkov luminescence imaging: a new tool for molecular imaging

Abstract: Cerenkov radiation is a phenomenon where optical photons are emitted when a charged particle moves faster than the speed of light for the medium in which it travels. Recently, we and others have discovered that measurable visible light due to the Cerenkov effect is produced in vivo following the administration of b-emitting radionuclides to small animals. Furthermore, the amounts of injected activity required to produce a detectable signal are consistent with small-animal molecular imaging applications. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
189
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(195 citation statements)
references
References 27 publications
(62 reference statements)
3
189
0
3
Order By: Relevance
“…Recently, Thorek et al demonstrated that significantly high sensitivity could be achieved with CLI as low amounts of 18 F-FDG accumulated (about 2Ci) in the nodes of patients 39,40 . In vitro testing indicated that CLI signal from 0.01 Ci 90Y was detectable in solution 25,32,33 . Moreover, CLI also has the potential for high spatial resolution and the capacity for high throughput screening.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Thorek et al demonstrated that significantly high sensitivity could be achieved with CLI as low amounts of 18 F-FDG accumulated (about 2Ci) in the nodes of patients 39,40 . In vitro testing indicated that CLI signal from 0.01 Ci 90Y was detectable in solution 25,32,33 . Moreover, CLI also has the potential for high spatial resolution and the capacity for high throughput screening.…”
Section: Discussionmentioning
confidence: 99%
“…In this protocol, we demonstrate that CLI with 18 F-FDG can be applied for optically imaging BAT in small animals. Like other optical imaging techniques, tissue penetrating limitation and low sensitivity for deep targets are the intrinsic limitations of CLI 25,32 . 39,40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ever since its discovery [3], Cherenkov light has become a tool useful in science ranging from physics [4] to biology [5]. Since spent nuclear fuel is frequently stored in water for radiation protection and heat removal, the radiation from the fuel will create Cherenkov light in the surrounding water.…”
Section: Introductionmentioning
confidence: 99%